The role of gamification-based learning on prospective teacher’s lower order thinking abilities - Rahim, Mujeebur; Mohammed, Lubna Ali; Tatlah, Ijaz Ahmad (Journal of Language and Pragmatics Studies, 2024)
Gamification has proved to be a highly effective educational technique for the twenty-first century. The study aims to explore the role of gamification-based learning on prospective teachers' lower-order cognitive abilities. This study used a qualitative exploratory research design, a literature review, and interviews. In order to investigate the function of gamification-based learning in prospective teachers' academic achievement covering lower-order cognitive abilities, the most recent research studies were reviewed, and a telephone interview was conducted with 12 participants. Purposive sampling was utilized to select a sample for the study. The interview data collected from prospective instructors was analyzed using thematic analysis. The literature review findings indicate that gamification-based learning contributes positively to educational success. No in-depth research has determined whether gamification-based learning practices can enhance students' academic performance in lower-order thinking skills. In addition, the main findings from the study's primary source, such as the interview with Kahoot-familiar trainee instructors, indicate that Kahoot-based gamification may provide opportunities to utilize lower-order thinking skills. It is also beneficial to enhance the lower-order cognitive abilities of prospective teachers by providing a competitive environment and immediate constructive feedback in a comfortable and enjoyable setting. Gamification-based learning can improve students' lower-order cognitive abilities. For the generalizability and authenticity of this exploratory study's findings, it is recommended to conduct an experimental study.